Effect of Different Levels of Rapeseed Meal Supplemented with Calcium Iodate on Performance, Some Carcass Traits, and Thyroid Hormones of Broiler Chickens - Maroufyan, E.; Kermanshahi, H. (International Journal of Poultry Science, 2006)
In a completely randomized design with 3*3 factorial arrangements and 4 replicates, 360 day-old Ross male broiler chickens were used to evaluate the effect of different levels of a locally grown rapeseed meal (RSM) supplemented with iodine on performance, organs weight and thyroid hormones of broiler chickens. The RSM was used at the levels of 0.0 (control), 7.5 and 15.0 percent for 7 weeks. The iodine levels added into the diets were 0.35 (NRC, 1994 recommendation, control), 0.75 and 1.05 mg/Kg. Feed intake and feed to gain ratio were affected by added levels of RSM during the starter (0-21 d), grower (21-42), finisher(42-49) and overall (0-49 d) feeding periods (P< 0.05). Body weight gain was not affected by treatments in any periods. Added high levels of RSM significantly increased the relative weights of liver, spleen (P< 0.05) and decreased the weights of abdominal fat pad (P< 0.05). Adding levels of RSM were also significantly increased the concentration of serum tri-idotyronine (T3) at 42 days of age and the concentration of serum thyroxin (T4) at 21 days of age (P< 0.05), while adding iodine into the diets had no significant effect among treatments. Thyroid-stimulating hormone (TSH) was not significantly affected by adding RSM into the diets at 21 and 42 days of age. Under the conditions of this study it was concluded that adding RSM into the diets of broilers decreases their performance. Spite the non significant effect of iodine on performance of broilers, due to the presence of glucosinolates in RSM, use of more iodine needs to be considered.